Enfoque integral del INTA para la gestión productiva del recurso hídrico - Benitez, Roger Alejandro; Mañueco, María Lucía; Riera, Felix Sebastián; Vita, Facundo (Instituto Nacional del Agua (INA), 2025)
Ponencia y poster.